Impact of the COVID-19 Pandemic on Excess Perinatal Mortality and Morbidity in Israel - Mor, Matan; Kugler, Nadav; Jauniaux, Eric; Betser, Moshe; Wiener, Yifat; Cuckle, Howard; Maymon, Ron (American Journal of Perinatology, 2020)
Objective The 2020 COVID-19 pandemic has been associated with excess mortality and morbidity in adults and teenagers over 14 years of age, but there is still limited evidence on the direct and indirect impact of the pandemic on pregnancy. We aimed to evaluate the effect of the first wave of the COVID-19 pandemic on obstetrical emergency attendance in a low-risk population and the corresponding perinatal outcomes.Study Design This is a single center retrospective cohort study of all singleton births between February 21 and April 30. Prenatal emergency labor ward admission numbers and obstetric outcomes during the peak of the first COVID-19 pandemic of 2020 in Israel were compared with the combined corresponding periods for the years 2017 to 2019.Results During the 2020 COVID-19 pandemic, the mean number of prenatal emergency labor ward admissions was lower, both by daily count and per woman, in comparison to the combined matching periods in 2017, 2018, and 2019 (48.6 ± 12.2 vs. 57.8 ± 14.4, p < 0.0001 and 1.74 ± 1.1 vs. 1.92 ± 1.2, p < 0.0001, respectively). A significantly (p = 0.0370) higher rate of stillbirth was noted in the study group (0.4%) compared with the control group (0.1%). All study group patients were negative for COVID-19. Gestational age at delivery, rates of premature delivery at <28, 34, and 37 weeks, pregnancy complications, postdate delivery at >40 and 41 weeks, mode of delivery, and numbers of emergency cesarean deliveries were similar in both groups. There was no difference in the intrapartum fetal death rate between the groups.Conclusion The COVID-19 pandemic stay-at-home policy combined with patient fear of contracting the disease in hospital could explain the associated higher rate of stillbirth. This collateral perinatal damage follows a decreased in prenatal emergency labor ward admissions during the first wave of COVID-19 in Israel.Key Points
Keywords: COVID-19; pandemic; IUFD; SARS-COV-2; stillbirth